2020
DOI: 10.1038/s41467-020-15068-4
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular localization of macrophages in the intestinal mucosa is regulated by Nr4a1 and the microbiome

Abstract: While the ontogeny and recruitment of the intestinal monocyte/macrophage lineage has been studied extensively, their precise localization and function has been overlooked. Here we show by imaging the murine small and large intestines in steady-state that intestinal CX3CR1 + macrophages form an interdigitated network intimately adherent to the entire mucosal lamina propria vasculature. The macrophages form contacts with each other, which are disrupted in the absence of microbiome, monocyte recruitment (Ccr2 −/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 52 publications
5
93
0
Order By: Relevance
“…It was shown experimentally that dietary components and obesity can directly perturb the intestinal barrier by changing tight junctions in the mucosa of the gut [99]. Furthermore, CX3CR1-expressing macrophages form a perivascular barrier in the intestine, which is disrupted in dysbiosis [179]. A recent study demonstrated that the presence of CX3CR1+ macrophages in the intestine had a protective effect in models of steatohepatitis and deficiency in CX3CR1 increased steatohepatitis by elevated endotoxin levels [180].…”
Section: Gut-liver Axismentioning
confidence: 99%
“…It was shown experimentally that dietary components and obesity can directly perturb the intestinal barrier by changing tight junctions in the mucosa of the gut [99]. Furthermore, CX3CR1-expressing macrophages form a perivascular barrier in the intestine, which is disrupted in dysbiosis [179]. A recent study demonstrated that the presence of CX3CR1+ macrophages in the intestine had a protective effect in models of steatohepatitis and deficiency in CX3CR1 increased steatohepatitis by elevated endotoxin levels [180].…”
Section: Gut-liver Axismentioning
confidence: 99%
“…LPM can be further subdivided into mucosal and submucosal LPM with different life span, transcriptional program, and functions (De Schepper et al, 2018 ). Mucosal LPM from the SI to the colon line the intestinal epithelium on the one hand and the vasculature on the other hand (Niess et al, 2005 ; Chieppa et al, 2006 ; Chikina et al, 2020 ; Honda et al, 2020 ). Mucosal subepithelial LPM are thus strategically positioned to sample luminal antigens and to protect the mucosa from enteropathogens that can penetrate the epithelial barrier.…”
Section: Tell Me Where You Live and I Will Tell You What Kind Of Macrmentioning
confidence: 99%
“…Another subpopulation of CX 3 CR1 + mucosal and also submucosal LPM is closely associated to the intestinal vasculature in mice (De Schepper et al, 2018 ; Honda et al, 2020 ). Perivascular LPM are either self-maintaining throughout adulthood, especially submucosal ones, or replaced by monocytes on a regular basis, especially mucosal ones (De Schepper et al, 2018 ).…”
Section: Tell Me Where You Live and I Will Tell You What Kind Of Macrmentioning
confidence: 99%
See 2 more Smart Citations